Discrimination and Prejudice Against Polish Immigrants in the Icelandic Labor Market A Survey Experiment - Helgi Magnússon 1973- (2021)
This thesis is about exploring data from a large sample from the Social Science Research Institutes’ (Félagsvísindastofnun) panel in Iceland in order to look for any evidence for or against discrimination against Polish Immigrants in the Icelandic labor market. Using a field survey experiment, participants rated Polish and Icelandic job applicants for jobs in the financial market, both in sales and management. Discrimination was observed with the wages offered and prejudice was observed through a list of questions relating to perceived qualifications. There was no evidence of wage discrimination detected, but the data showed a compelling reason to believe prejudice to be in place. Viðskiptafræðideild hefur samþykkt lokaðan aðgang að þessari ritgerð í 2 ár.